Challenges for Drug Repurposing in the COVID-19 Pandemic Era - Sultana, Janet; Crisafulli, Salvatore; Gabbay, Flic; Lynn, Elizabeth; Shakir, Saad; Trifirò, Gianluca (Frontiers in Pharmacology, 2020)
The coronavirus disease (COVID-19) pandemic has affected an estimated 16 million persons and caused 0.6 million deaths worldwide. The pandemic has led to a rush to repurpose existing drugs, although the underlying evidence base is of variable quality. The improving knowledge of the virology and clinical presentation of COVID-19 is leading to a broadening pool of potential pharmacological targets. The aim of this review is to describe regulatory and pharmacological aspects of drug repurposing and to identify drugs proposed for repurposing in COVID-19 based on registered clinical trials, discussing the evidence to support their use in the treatment of this disease. The challenges of the correct interpretation of existing pre-clinical/ clinical evidence as well as the generation of new evidence concerning drug repurposing in COVID-19 will also be discussed.